The marriage portrait - O'Farrell, Maggie, 1972- (New York : Alfred A. Knopf, 2022)
"A novel set in Renaissance Italy, and centering on the captivating young duchess Lucrezia de' Medici. When her older sister dies on the eve of her wedding to the duke, Lucrezia is is thrust unwittingly into the limelight: the duke is quick to request her hand in marriage and her father just as quick to accept on her behalf. Having barely left girlhood behind, Lucrezia must now make her way in a troubled court whose customs are opaque and where her arrival is not universally welcomed."--
"A Borzoi book."
Includes bibliographical references (pages 338-339).
Keywords: Medici, Lucrezia de', -- 1545-1561 -- Fiction; Renaissance -- Italy -- Florence -- Fiction; Florence (Italy) -- History -- 1421-1737 -- Fiction; Biographical fiction; Historical fiction